Dari Sampah Menjadi Rupiah: Strategi Pemberdayaan Pemulung melalui Daur Ulang Kreatif Berbasis Ekonomi Sirkular - Triyono Arief Wahyudi; Wakhyudin Wakhyudin; Andi Aditya Hardinto (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2025)
Urban waste management has become a critical issue requiring innovative and sustainable solutions. Informal waste pickers play a strategic role in reducing waste accumulation; however, they often face limitations in economic capacity and technical skills. This community service program aims to empower waste pickers through training and mentoring in transforming waste into value-added products in Pancoran Barat IX Street, South Jakarta. The program employed a participatory approach consisting of problem identification, socialization, and training, assistance, and evaluation stages. The results indicate a significant improvement in participants’ knowledge and skills in productive waste management, leading to the creation of recycled products with higher market value compared to raw waste materials. Furthermore, the program encouraged behavioral changes in waste sorting practices and enhanced environmental awareness. Economically, participants experienced additional income, although still at a modest level. Therefore, this initiative demonstrates strong potential as a community empowerment model based on circular economy principles, contributing not only to improved livelihoods but also to sustainable environmental management.